Faktor-faktor yang Mempengaruhi Kinerja Kewirausahaan Petani Kopi Arabika di Kecamatan Dolog Masagal, Kabupaten Simalungun, Provinsi Sumatera Utara: Factors Affecting the Entrepreneurial Performance of Arabica Coffee Farmers in Dolog Masagal District, Simalungun Regency, North Sumatra Province - Jef Rudiantho Saragih; Ummu Harmain (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
Arabica coffee is a leading commodity in Simalungun Regency, where entrepreneurship becomes one of the important aspects in arabica coffee farming management. This study aims to understand the influence of internal factors (farmer age, education, experience, number of family members, family motivation, and work culture) and external factors (government support, community support, access to production facilities, and climatic conditions) on entrepreneurial performance of arabica coffee farmers. The research was conducted in two villages (Bangun Pane village and Bintang Mariah village) in Dolog Masagal district, Simalungun Regency, North Sumatra Province during March to May 2018. The study sample covers 60 farmer households who have Arabica coffee farming with at least 300 arabica coffee plants and minimum plant age of three years, determined by snowball sample method. The study used ratio and scale data (Likert scale), which was analyzed using multiple regression equations. Data were processed using SPSS 24. Results show that internal factors have positive and significant effect on the entrepreneurial performance of arabica coffee farmers (value Sig.=0.005), while external factors have positive and insignificant effect (value Sig.=0.313). Local governments through relevant technical agencies are recommended to provide facilitation in improving farmers' access to production factors, increasing quantity and quality of extension, technical guidance, and relevant training.